The Relationship Between The Use Of Gadget With The Emotional Intelligence Of School Age Children During Covid-19 Pandemic - Rehana; Nurul Komariah; Khalda Tiara Putri (International Journal of Health Engineering and Technology, 2023)
Excessive use of gadgets in children can have a negative effect on children's cognitive and emotional development. The results of the APJII survey (Association of Indonesian Internet Service Providers) explain that the penetration of internet users in Indonesia is increasing every year. From the BPS survey, it was found that internet users aged 10-14 years amounted to 8.31% in 2019. Research Objectives: To determine the relationship between the use of gadgets and the emotional intelligence of school-age children (10-12 years) during the Covid-19 pandemic at SD Negeri 59 Palemban. This study used a cross sectional design. Samples were taken according to the inclusion criteria, totaling 60 respondents with Stratified Random Sampling. Data analysis used univariate, bivariate analysis, namely, Chi-Square test. Based on the results of the analysis, it can be seen that children who have low levels of gadget use and emotional intelligence are sufficient, there are 15 respondents (45.5%) out of 33 respondents, lower when compared to children who use gadgets high and emotional intelligence is sufficient, there are 24 respondents (88.9%) ) of 27 respondents. The results of the Chi-Square test obtained p-value = 0.001 (α ≤ 0.05), so it can be concluded that there is a relationship between the use of gadgets and the emotional intelligence of children aged 10-12 years during the Covid-19 pandemic at SDN 59 Palembang in 2021. There is a relationship between the use of gadgets on the emotional intelligence of school-age children (10-12 years)